Kyrgyz Republic : Fourth and Fifth Reviews under the Three-Year Arrangements under the Extended Credit Facility, and Request for Modification of Performance Criteria-Press Release; Staff Report. (IMF Staff Country Reports; Country Report ;, 2018)
A moderate economic recovery is underway, driven by higher gold production, remittances, and growth in key trading partners. The recent tightening of controls on the border with Kazakhstan will have some limited impact on the economy this year but could weaken trade and growth substantially if it persists. Inflation is normalizing with the rise of food prices. The banking sector is showing signs of recovery but vulnerabilities remain. The October elections slowed reforms and put additional pressure on the budget, although the government has since taken offsetting measures. Public debt remains at moderate risk of distress, helped by som appreciation. The fourth review under the Extended Credit Facility (ECF) arrangement, which was originally scheduled to be completed in June, could not be completed on time. Since then, the authorities have taken corrective measures, which paved the way for moving forward with the combined fourth and fifth reviews.